Pregnancy planning health information and service needs of women with chronic non-communicable conditions: a systematic review and narrative synthesis - Karin Hammarberg; Ruby Stocker; Lorena Romero; Jane Fisher (BMC, 2022)
Abstract Background Preparing for pregnancy and being in the best possible health before conception improves reproductive outcomes. For women living with a chronic non-communicable disease (NCD), pregnancy planning is essential to allow optimal disease control in preparation for pregnancy. Aim The aim was to review the literature relating to the pregnancy planning health information and service needs of women with NCDs. Method The MEDLINE (Ovid), Embase (Ovid), Emcare (Ovid), PsycINFO (Ovid), CINAHL and Scopus databases were searched. Studies were included if they were published in peer-reviewed English language journals between January 2010 and June 2020 and reported on the pregnancy planning health information and service needs of women with rheumatic diseases, asthma, cystic fibrosis, depression and/or anxiety, type 1 diabetes mellitus, epilepsy, or multiple sclerosis. Risk of bias was assessed using QualSyst. The characteristics of the studies were tabulated and summarised. Key findings of the included studies were analysed thematically using an inductive approach, where the study findings determined the themes. Findings are reported in a narrative synthesis. Results The database searches yielded 8291 results, of which 4304 remained after duplicates were removed. After abstract screening 104 full-text papers were reviewed. Of these 15 met inclusion criteria and were included in analysis. The narrative synthesis of the included studies revealed six themes: 'Women with chronic conditions have unmet preconception health information needs', 'Women with chronic conditions want personalised preconception health information', 'Preferred sources of preconception health information', 'Learning from the experiences of other women', 'Improving preconception health discussions with health care professionals', and 'Women want holistic care'. These themes were consistent across all studies, highlighting the similarity of experiences and needs of women with different chronic conditions. Conclusion To improve pregnancy outcomes for women living with NCDs, health care providers need to ask women of reproductive age proactively and routinely about their pregnancy intentions and provide them with personalised advice on how to avoid unplanned pregnancy and be in optimal health when they wish to conceive. PROSPERO registration number CRD42020176308.